LITERARY TRAUMA THEORY IN MAYA ANGELOU’S I KNOW WHY THE CAGED BIRD SINGS - Neyah , Ruth; M, Vijayakumar (International Journal of Psychosocial Rehabilitation, 2020)
The desideratum of this study is to evaluate the literary trauma theory which strikes ably in the works of Maya Angelou, predominantly in her first autobiography I know why the caged bird sings. Maya Angelou unveils the desperate traumatic encounters of her life almost in all her works. Literary Trauma Theory basically aims at flashing the background of the trauma experienced by the writer while penning the autobiography. The trauma studies related to this area were brought into the limelight by Cathy Caruth, a renowned author and professor at Cornell University. The text considered for the study exhibits the past and the epoch-making hardships in life which Maya Angelou has faced, that has infused within her the attribute of forbearance, tenacity, and firmness of purpose. The main objective of this study is to analyse the concept of literary trauma theory as it plays a pivotal role in fabricating the concept of the texts written by Maya Angelou, which has a firm background interconnected to her life story.